THE EFFORTS OF MIXED COUNTING STORY QUESTIONS LEARNING THROUGH CONSTRUCTIVISM APPROACH TO MATHEMATICS SUBJECTS FOR 4TH GRADE SDN SARUNI 4 - Rima Maspriana; Nunung Nunung (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2021)
Abstract This research was motivated by teachers who were not satisfied with the results obtained from mixed counting story problems learning in elementary schools. Therefore, the problem being studied is how the influence of story problems learning using the constructivism approach for 4th grade of SDN Saruni 4. The method used is a qualitative method with classroom action research techniques (action research). The techniques of data collection were carried out using instruments in the form of student worksheets, observation sheets, interview guidelines, field notes, and photo cameras, then the data obtained were analyzed and reflected. This research was conducted in two cycles; each cycle was carried out according to the changes wants to be achieved, as what had been designed in the investigated factors. The skills developed include the ability to solve story problems of addition and subtraction mixed counting operations. The average score of the pre-cycle is 54.71, the first cycle is 71.76, and the second cycle obtains 85.88. Thus, the mastery level of students' concepts about story problems with the constructivism approach has increased generally. Based on the research results obtained, it can be concluded that mixed counting story problems learning through the constructivism approach are successful. Keywords: Mixed Counting Story Problems; Constructivism Approach